Czech Republic as A Deferring Factor for European Union to Achieve Climate Change Measures - Mada, Kris Razianto; Nugrahani, Henny Saptatia Drajati (UI Scholars Hub, 2022)
This study aims to finds out causal factors for Czech Republic yet to decide on phasing out coal-fired power plant and the impact of delaying the preparation of the coal-fired power plant phase-out plan by Czech on the EU's goal of reducing greenhouse gas emissions. The researcher conducts an analysis based on two research questions: what are causal factors for Czech Republic yet to decide on phasing out coal-fired power plant and what impact will it have on the EU's efforts to reduce greenhouse gas emissions by 2030 and become fully carbon neutral by 2050. The method used in this study is descriptive qualitative approach and literature review. The findings of this study are as follows: first, environmental and health reasons are the main reasons for the EU's decision to phasing out coal and other forms of fossil energy. The EU targets to cut emissions by 2030 and become fully carbon neutral by 2050. Second, Yet, Prague continues to mine coal since it is the only domestic-energy-source and made Czech become energy exporter. Czech has to import crude oil, natural gas and uranium for nuclear reactors. Third, Coal survives in Czech as politician and former politician support it. Czech coal industry also indirectly received support from the local mass media. Czech mass media almost never associate coal issues with climate change and other environmental and health issues. Concern on coal in Czech Coal often raised from the perspective of job opportunities, regional economic resilience, and energy security.